Sexual dysfunction in patients with MDD treated with SSRIs - causes, measurement and prevention - Giermasinski, Adrian; Próchnicka, Magdalena; Nowak, Dominika; Oszczędłowski, Paweł; Nowaczek, Justyna (Journal of Education, Health and Sport, 2021)
Major Depressive Disorder(MDD) is serious psychiatric condition and they affect one in five people during their lifetime, the annual prevalence rates for the US population are 7.1% among adults, slightly more common among women (8.7%) than men (5.3%). Selective serotonin reuptake inhibitors are among the pharmacological agents most commonly used in the treatment of MDD. The mechanism of action of antidepressants is not yet fully understood. Currently, it is believed that the mechanism of the so-called down-regulation, i.e. reducing the density of receptors in the postsynaptic membrane, in this case mainly 5HT2 receptors. All of the antidepressants in use today have some common side effects. The side effect that will be discussed in the broadest possible way in this paper are sexual dysfunctions appearing during the therapy. Measuring the degree to which a given substance affects the sexual function of a patient diagnosed with MDD encounters many difficulties on its way. There are currently several questionnaires enabling such an assessment, the most common are CSFQ, ASEX and SexFX. Also the major problem is Post SSRI Sexual Disfunction. A number of animal studies have proven that prolonged exposure to SSRIs leave permanent changes in the CNS, but unfortunately, similar studies have not yet been conducted in humans. The aim of this study is to present the problem of sexual dysfunction as a side effect of SSRI therapy, to present the causes and to propose a strategy to combat SSRI-induced sexual dysfunctions.